2015
DOI: 10.1371/journal.pgen.1005025
|View full text |Cite
|
Sign up to set email alerts
|

Linking Aβ42-Induced Hyperexcitability to Neurodegeneration, Learning and Motor Deficits, and a Shorter Lifespan in an Alzheimer’s Model

Abstract: Alzheimer’s disease (AD) is the most prevalent form of dementia in the elderly. β-amyloid (Aβ) accumulation in the brain is thought to be a primary event leading to eventual cognitive and motor dysfunction in AD. Aβ has been shown to promote neuronal hyperactivity, which is consistent with enhanced seizure activity in mouse models and AD patients. Little, however, is known about whether, and how, increased excitability contributes to downstream pathologies of AD. Here, we show that overexpression of human Aβ42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 69 publications
4
50
0
Order By: Relevance
“…In this report, we use a transgenic Drosophila line that overexpresses a secreted form of the human Ab42 peptide as a model to examine the effects of Ab42 on cholinergic synaptic function and to gain insight into the potential role of homeostatic mechanisms driving Ab-induced adaptive and maladaptive changes in cholinergic activity. These flies exhibit many of the pathogenic hallmarks associated with AD (Finelli et al, 2004;Iijima et al, 2004Iijima et al, , 2008Ping et al, 2015). We show that both Ab40 and Ab42 induce an early enhancement in spontaneous cholinergic synaptic events and that this increased activity is followed by a subsequent reduction in spontaneous events, a progression that parallels what has been suggested to occur in cholinergic regions of mammalian AD models.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…In this report, we use a transgenic Drosophila line that overexpresses a secreted form of the human Ab42 peptide as a model to examine the effects of Ab42 on cholinergic synaptic function and to gain insight into the potential role of homeostatic mechanisms driving Ab-induced adaptive and maladaptive changes in cholinergic activity. These flies exhibit many of the pathogenic hallmarks associated with AD (Finelli et al, 2004;Iijima et al, 2004Iijima et al, , 2008Ping et al, 2015). We show that both Ab40 and Ab42 induce an early enhancement in spontaneous cholinergic synaptic events and that this increased activity is followed by a subsequent reduction in spontaneous events, a progression that parallels what has been suggested to occur in cholinergic regions of mammalian AD models.…”
Section: Introductionsupporting
confidence: 63%
“…These opposing changes are intriguing because mammalian Ab models have also been reported to exhibit both increases and decreases in spontaneous activity; however, little is known about how these opposing effects are induced and how they are related. Since previous studies using this transgenic line have shown that significant neuronal loss is not observed in Ab42-expressing brains until 25 days AE (Iijima et al, 2004;Ping et al, 2015), the decrease in synaptic activity seen at 9-13 days AE may be due to synaptic dysfunction that precedes neuronal death. Since in vitro experimental conditions would allow for pharmacological as well as genetic manipulation, we tested whether similar activity changes could be observed in primary neurons cultured from the same genetic lines.…”
Section: Ab42 Exerts An Early Increase In Cholinergic Synaptic Activimentioning
confidence: 81%
See 1 more Smart Citation
“…A recent study also described the selective degradation of Kv4 channels in flies expressing Aβ42 leading to neuronal hyperactivity (Fig. 3) (Ping et al, 2015). Reducing the levels of Kv4 channels led to locomotor defects whereas Kv4 overexpression rescued Aβ42 neurotoxicity, supporting a critical role for K + channel activity in Aβ42 pathogenesis.…”
Section: Drosophila Models Of Aβ42 Neurotoxicitymentioning
confidence: 79%
“…In Drosophila, neuronal overexpression of different human APP products (including A42) and mutants has been reported to cause degeneration of the photoreceptor neurons of the fly eye, shortened lifespan, change in neuronal excitability as well as movement, circadian, sleep and learning defects in a number of different studies [26][27][28][29][30][31][32]. Likewise, neuronal overexpression of human Tau isoforms associated with AD have been shown to result in degeneration of the photoreceptor neurons of the fly eye, shortened lifespan, movement and learning defects in many different studies [33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%